2003 IEEE National Symposium on Microelectronics (NSM 2003) : proceedings : September 9 - 10, 2003, Putra palace Hotel, Kangar, Perlis, Malaysia - IEEE National Symposium on Microelectronics (2003 : Perlis, Malaysia); Rahman Wagiran; Burhanuddin Yeop Majlis, editor; IEEE Malaysia Section; Institute of Microengineering and Nanoelectronics (IMEN), UKM; Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM); Silterra Malaysia Sdn. Bhd; Perlis State Government (Bangi : IEEE Malaysia Section, 2003)
16